Cell adhesion - edited by Mary C. Beckerle (Oxford University Press, 2001)
Cell adhesion plays a central role in development and disease. Cell adhesion to particular ligands can affect cytoskeletal organization and cell polarity, cell proliferation, and gene expression. This book is divided into two parts. The first section provides a discussion of the structure and function of the seven major classes of cell adhesion molecules: integrins, cadherins, selectins, heparan sulfate proteoglycans, the immunoglobulin superfamily, the ADAMs proteins, and transmembrane protein tyrosine phosphatases. The roles of these cell adhesion proteins in important processes such as cell mediated immunity, development and disease are discussed. In the second section, the molecular organization and function of junctional complexes, regions of the cell surface that are highly specialized for cell adhesion, are examined. Junctional complexes are now known to mediate adhesive interactions and contribute to transmembrane signaling events that dramatically influence cell behaviour. The biochemical organization of the adhesive membranes and the molecular mechanisms by which they transmit information to the cell are addressed. Written by contributors among the most prominent in the field, Cell Adhesion covers a wide range of topics in a single volume. It will be a great resource for students, teachers and researchers